Strategi Bauran Pemasaran Dalam Meningkatkan Volume Penjualan Pada PT Mandiri Utama Finance Cabang Kediri - Akbar, Ali; Nirawati , Lia (Jurnal Bisnis dan Ekonomi, 2024)
This study uses PT Mandiri Utama Finance Kediri branch, a company engaged in multipurpose financing, as the research object. The purpose of this research is to provide an analysis of the marketing strategy implemented by PT Mandiri Utama Finance Kediri branch to increase sales volume. The results of the SWOT analysis are used as the basis for determining the marketing strategy that PT Mandiri Utama Finance Kediri branch can implement to increase sales volume. The research method used is descriptive with a qualitative approach, using data collection techniques through observation and in-depth interviews. These techniques relate to the marketing mix strategy, which includes product, price, place/distribution, promotion, people/human resources, process, and physical appearance. This strategy is used by researchers to identify strengths, weaknesses, opportunities, and threats through the SWOT analysis method at PT Mandiri Utama Finance Kediri branch. From the research conducted, the IFAS results show strengths of 2.95 and weaknesses of 0.34. Meanwhile, the EFAS results show opportunities of 2.36 and threats of 1.00. The chosen strategic outcome is the SO strategy, where on the SWOT diagram it is located in Quadrant I, meaning the company has opportunities and strengths, thus can maximize the existing opportunities. Therefore, the strategy that should be implemented is to support an aggressive growth-oriented strategy. Keywords: Finance, Marketing Mix Strategy, SWOT Analysis, IFAS Matrix, EFAS Matrix.